서울특별시 초·중·고등학생의 비흡연 의지에 영향을 미치는 요인 - 황지은(Jieun Hwang); 정한나(Hanna Jung); 양예슬(Yeaseul Yang); 권수현(Suhyun Kwon); 전해령(Hae-ryoung Chun); 김승완(Seungwan Kim); 제갈정(Jung JeKarl); 유승현(Seunghyun Yoo); 조성일(Sung-il Cho) (보건교육건강증진학회지, 2020)
Objectives: This study investigated factors affecting the future non-smoking intentions of students who had received smoking prevention education in school. Methods: After receiving data collected via a repeated cross-sectional, three-year operation survey of Seoul Metropolitan City conducted from 2016 to 2018 by the Korea Health Promotion Institution, hierarchical logistic regression was performed to identify factors affecting future non-smoking will. Results: Adolescents’ willingness to not smoke was higher among females and middle school students than among males and high school students, respectively. Additionally, the willingness not to smoke among students was positively correlated with the absence of tobacco use in their lifetime, currently being a non-smoker, awareness of smoking-ban school policies, lack of experience of witnessing on-campus smoking, and lack of indirect smoke exposure in their homes. Those who had received smoking prevention education had a stronger willingness to not smoke as compared to those who had not. Conclusion: In order to dissuade and prevent students from smoking, efforts at the school, community, and national levels are required to minimize the exposure of young people to smoking and tobacco products. The methods and contents used in smoking prevention education must also be further considered. KCI Citation Count: 1